Performance evaluation of intermittently CFRP wrapped square and circularised square reinforced concrete columns under different loading conditions. Issue 5 (4th May 2019) - Mai, Anh Duc; Sheikh, M. Neaz; Hadi, Muhammad N. S.
Abstract: This paper presents the results of an experimental investigation on square and circularised square reinforced concrete (RC) columns intermittently wrapped with carbon fibre reinforced polymer (CFRP) under different loading conditions. Twelve RC specimens consisting of eight square RC specimens with 150 mm × 150 mm cross-section and 800 mm height and four circularised square RC specimens with 212 mm diameter and 800 mm height were tested under concentric axial load, eccentric axial load and four-point flexural load. The test results showed that intermittent wrapping increased the strength and ductility of square RC specimens. The test results also showed that circularisation combined with intermittent wrapping significantly improved the strength and ductility of square RC specimens. The experimental axial load-bending moment interaction diagram showed that the best performance was achieved by intermittently CFRP wrapped circularised square RC specimens.